2015
DOI: 10.3389/fendo.2015.00090
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Oxytocin in the Etiology and Treatment of Schizophrenia

Abstract: Schizophrenia is a chronic debilitating neuropsychiatric disorder estimated to affect 51 million people worldwide. Several symptom domains characterize schizophrenia, including negative symptoms, such as social withdrawal and anhedonia, cognitive impairments, such as disorganized thinking and impaired memory, and positive symptoms, such as hallucinations and delusions. While schizophrenia is a complex neuropsychiatric disorder with no single “cause,” there is evidence that the oxytocin (Oxt) system may be dysr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 209 publications
(243 reference statements)
1
25
0
8
Order By: Relevance
“…Considering the role of the amygdala and septum in the antidepressant/anxiolytic actions of OT (Curley et al ., ; Zanos et al ., ), the upregulation of the OTR binding in these regions may represent a neuroadaptive response of the oxytocinergic system to counteract the negative consequences of cocaine administration/withdrawal. Indeed, OT administration has been shown to reduce anhedonia in schizophrenic patients (see Rich & Caldwell, ) and to induce a hedonic state in rodents (see Slattery & Neumann, ). Therefore, dysregulation of the OTR system might contribute to the development of anhedonia observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of the amygdala and septum in the antidepressant/anxiolytic actions of OT (Curley et al ., ; Zanos et al ., ), the upregulation of the OTR binding in these regions may represent a neuroadaptive response of the oxytocinergic system to counteract the negative consequences of cocaine administration/withdrawal. Indeed, OT administration has been shown to reduce anhedonia in schizophrenic patients (see Rich & Caldwell, ) and to induce a hedonic state in rodents (see Slattery & Neumann, ). Therefore, dysregulation of the OTR system might contribute to the development of anhedonia observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, increased methylation of OXTR may lead to abnormal gene expression that disrupts hippocampal and/or medial prefrontal cortex function and causes cognitive impairment (e.g., memory deficits and/or impaired emotion recognition) [see [56] for a review]. This disruption may be exacerbated by psychosocial stressors, which can increase OXTR methylation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Work from our lab using Oxt −/− mice found that male and female Oxt −/− mice treated with the psychotomimetic phencyclidine, an NMDA receptor antagonist, have greater PPI deficits than controls (Caldwell et al, ). These data suggest that Oxt may have some antipsychotic properties and directly affect the PPI circuitry (Rich and Caldwell, ; Feifel et al, ). While Oxt is not thought to be the cause of a complicated neuropsychiatric disorder like schizophrenia, it may be an important player in the etiology of some forms of schizophrenia (Rich and Caldwell, ).…”
Section: Oxytocin and Nonsocial Behaviorsmentioning
confidence: 99%
“…These data suggest that Oxt may have some antipsychotic properties and directly affect the PPI circuitry (Rich and Caldwell, ; Feifel et al, ). While Oxt is not thought to be the cause of a complicated neuropsychiatric disorder like schizophrenia, it may be an important player in the etiology of some forms of schizophrenia (Rich and Caldwell, ). We are hopeful that the use of KO mouse models of the Oxt system will help to identify specific neural substrates on which Oxt may act to affect behaviors that are relevant to neuropsychiatric disorders.…”
Section: Oxytocin and Nonsocial Behaviorsmentioning
confidence: 99%